Increasing Customer Purchase Intention through Sales Promotions on Sodai Ramen Yogyakarta’s Instagram in 2025 - Pingkan Wulandari; Sovia Sitta Sari (Jogjakarta Communication Conference (JCC), 2026)
This study aims to analyze how sales promotions through Sodai Ramen Yogyakarta’s Instagram can increase customer purchase intention. The background of this study is the increasing competition in the ramen culinary business in Yogyakarta, which encourages business owners to utilize digital platforms as promotional channels. This study employs a descriptive qualitative method, with data collected through interviews and documentation. The results show that sales promotions conducted via Instagram play a significant role in building attention, interest, search, action, and sharing, in accordance with the AISAS model. Furthermore, the implementation of sales promotion through content strategies reflects the application of pull marketing, where consumers are attracted by engaging content offering bundled packages and high-quality menu options at affordable prices. Consumers actively seek information before making a purchase decision. This study highlights the importance of marketing communication strategies, particularly in sales promotion within the food and beverage industry through social media.